An other kingdom departing the consumer culture - Block, Peter; Brueggemann, Walter 1933-2025; McKnight, John 1931- (Wiley, 2016)
The Other Kingdom is about reframing how society views its communal identity. The book proposes to identify what has been considered sacred language and use it as an opening into the experience of community and the commons. It lays out a faith narrative without the negative traces of sectarianism. Readers are dared to imagine the human benefit of an alternative to the market ideology that defines our culture, called the Neighborly Covenant because it enlivens and humanizes the social order. The Other Kingdom proposes language for alternative ways to a covenantal culture, one that is active beyond election years and has different substance in defining society's communal identity.